Study on the Influence of Physical Activity Intensity and Maturation on Sports Injuries in Children and Adolescents - Lara Costa e Silva; Ana Lúcia Silva; Júlia Teles; Isabel Fragoso (Applied Sciences)
Intensive training combined with a growing body can predispose children to sports injuries. Our aim was to identify the importance of physical activity (PA) intensity and maturity as predictors of injury in youth. Information about injuries was collected using a questionnaire (LESADO), the PA intensity was assessed via accelerometry, and maturity was assessed using the Tanner–Whitehouse III bone age method and maturity offset. A total of 121 participants aged between 10 and 18 years were selected from four different schools. Regression analyses were used to determine the significant predictors of the injury profile. Only the injury type presented significant results. The time spent on moderate PA (χ2(2) = 6.701, p = 0.035) and bone age (χ2(2) = 7.196, p = 0.027) were the final predictors. The odds of having a strain or a fracture relative to a sprain increased 1.04 times for each minute of time spent on moderate PA. Likewise, the odds of having a strain or a fracture relative to a sprain decreased by 1.7 times per year of bone age. The PA intensity and bone age proved to be injury predictors in the growing athletes, with more predictive power in injury type. No meaningful associations were found for the injury occurrence, injury rate and body area injury location.